2000
DOI: 10.1063/1.1308276
|View full text |Cite
|
Sign up to set email alerts
|

Orientation dependence of the ferroelectric and piezoelectric behavior of Ba(Ti1−xZrx)O3 single crystals

Abstract: The dielectric properties, ferroelectric polarization, and piezoelectric strain behavior of Ba(Ti1−xZrx)O3 (x=0.05 and 0.08) single crystals are studied for different crystal orientations. The study of dielectric properties suggests that the three phase transitions in BaTiO3 are pinched by substituting Ti with Zr but the anisotropic dielectric behavior is present in crystals of various orientations. The remnant polarization and strain behavior are also studied for different crystal directions. Higher strain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(58 citation statements)
references
References 11 publications
5
48
0
Order By: Relevance
“…This suggests that the paraelectric to ferroelectric phase transition has shifted to lower temperatures while the temperatures from the tetragonal to orthorhombic transition (T O-T ) and the temperature of orthorhombic to rhombohedral transition (T R-O ) have moved upward with increasing hafnium concentration in the compounds. This well known pinching effect for the three phase transitions of pure barium titanate has also been found in Zr-doped BaTiO 3 system and Ce-doped BaTiO 3 [7,8]. From the experiment, it was found that the dielectric loss was also dependent of temperature as it was clear that such loss was lower when the doping hafnium in the compounds was measured at higher temperatures above 100 • C. However, no apparent frequency dispersion was observed for the dielectric constant when the samples were measured at different frequencies from 100 Hz to 1 MHz at room temperature.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…This suggests that the paraelectric to ferroelectric phase transition has shifted to lower temperatures while the temperatures from the tetragonal to orthorhombic transition (T O-T ) and the temperature of orthorhombic to rhombohedral transition (T R-O ) have moved upward with increasing hafnium concentration in the compounds. This well known pinching effect for the three phase transitions of pure barium titanate has also been found in Zr-doped BaTiO 3 system and Ce-doped BaTiO 3 [7,8]. From the experiment, it was found that the dielectric loss was also dependent of temperature as it was clear that such loss was lower when the doping hafnium in the compounds was measured at higher temperatures above 100 • C. However, no apparent frequency dispersion was observed for the dielectric constant when the samples were measured at different frequencies from 100 Hz to 1 MHz at room temperature.…”
Section: Resultsmentioning
confidence: 82%
“…Tel. : +852 27665671; fax: +852 23337629. largely improve the overall properties of the material [3][4][5][6][7][8]. For example, BaZr x Ti 1−x O 3 (BZT) has a small leakage current as a result of its better chemical stability of Zr 4+ than Ti 4+ and thus, is a suitable material for ceramic capacitors.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on single crystals have confirmed the improved piezoelectric response along the same crystallographic directions as predicted by theory. [7][8][9][10][11] While the intrinsic piezoelectric contribution and the rotator/extender nature are equal for a single crystal and an ideally textured ceramic with the same composition, the extrinsic piezoelectric properties are not. Intergranular interactions, which are not present in single crystals, contribute significantly to the piezoelectric effect in polycrystals.…”
Section: Introductionmentioning
confidence: 99%
“…The perovskite-type barium zirconate titanate, BaTi 1−x Zr x O 3 (BTZ), has attracted considerable attention as a possible lead-free ferroelectric material to replace the current industry standard lead-based ferroelectrics 1,2,3,4,5,6 . The particularity of BTZ is the continuous change of its properties from a ferroelectric behavior at low Zr substitution rates to a relaxor ferroelectric (relaxor) behavior at higher substitution rates (0.25 ≤ x ≤ 0.5) 7 .…”
Section: Introductionmentioning
confidence: 99%